Concrete Subjected to Varying Confinement, II: Modeling - Cetisli, Fatih; Naito, Clay J. (Japan Concrete Inst, 2009)
A unique model for estimating the axial response of concrete under varying or constant levels of confinement is developed. The proposed model is empirically developed from a companion experimental study of concrete tested under linear, elastic perfectly plastic (EPP), elasto-plastic with strain hardening, and constant triaxial confinement. The axial stress-strain response is divided into three regions separated by two characteristic response levels. The model is based on the variation of the confining pressure due to the lateral dilation of the concrete. An estimate of dilation with respect to axial strain is also developed. The model is shown to provide an accurate prediction of historical experimental studies of constant confinement tests on cylinders, fiber reinforced polymer (FRP) jacketed specimens, and columns confined with conventional lateral reinforcement or FRP jacket.
Keywords: High-Strength Concrete; Behavior